A Rare Variation of the Heterotaxy Syndrome. (28th June 2012) - Dilli, Alper; Gultekin, Salih Sinan; Ayaz, Umit Yasar; Kaplanoglu, Hatice; Hekimoglu, Baki
Abstract : Heterotaxy syndrome is a rare, complex, and confusing type of the situs anomalies. It is not possible to estimate the degree of lateralization, isomerism, and rotational variation in these types of cases. Heart and abdominal organ anatomy is specific to the individual, and it should be defined specifically on the basis of each case due to possible cardiac and extracardiac surgical interventions in patients with heterotaxy syndrome. Here, we present our findings obtained from a 58-year-old female patient with heterotaxy syndrome. The main components of this rare variation consist of right-hand-sided aorta, aortic arc, cardiac apex, gall bladder and left-hand-sided inferior vena cava, stomach, and spleen (polysplenia, 3 foci) according to the midline. Besides, the components include left-dominant liver, right-hand-sided large intestines, and left-hand-sided small intestines.